PROJECT APPLICATION UNTUK SISTEM PEMESANAN DAN PENGIRIMAN BARANG BERBASIS WEB PADA PT. ARAI RUBBER SEAL INDONESIA - Aris Martono; Solehudin Solehudin; Fajar Januar Eka Putra (UNIVERSITAS RAHARJA, 2017)
The development of science and technology is now increasingly rapid development, the need masyarakatakan akan information technology is increasing as well in the business world that tend to be dynamic and always changing in accordance with the times, consumer needs, andthe marketing environment, resulting in the large market demand. On the other hand emerging similar businesses that cause high levels of competition. PT. Arai Rubber Seal Indonesia is one type of company engaged in automotive spare parts industry. To support the automotive industry The company is growing quite rapidly, can be seen from the order of goods that enter quite a lot. Therefore, the company strives to improve the quality of its products also improve the system of ordering information and delivery of goods. In designing this system the author uses evolutionary prototype method because the author wants the prototype is still used for the next design iteration. In this case, the actual system is seen as an evolution from a very limited initial version to the latest evolution that better than using the author's prototype method also uses the design method. In this system the authors do the design method using UML (Unified Modeling Language) method because by using UMLmethod, engineering and device development can be done with the focus of development and design software it is also author With the analysis of information systems marketing and ordering goods expected to improve the activity Ordering and delivery of goods in order to compete to achieve company goals.